UTILIZATION OF CLOUD COMPUTING TECHNOLOGY TO OPTIMIZE COMMUNITY ADMINISTRATIVE SERVICES IN TIMUHUN VILLAGE, KUNGKUNG, BALI - Gama, Adie Wahyudi Oktavia; Bunga, Melania Pritama; Maulidan, Bagus; Permana, Gusi Putu Lestara (LPPM Univ. Ibn Khaldun Bogor, 2023)
To improve the performance of the village government to be able to provide easy and fast population administration services for rural communities, it is necessary to increase the literacy of Cloud Computing technology for Village Government officials. The purpose of this service activity is to improve the performance of the Village Government, especially the Village of Timuhun Klungkung Bali by utilizing Cloud Computing technology for better administrative services to the community. The method used is to provide education to Village Office officials about how to use various Cloud Computing Technology services, especially Google Workspace for population administration. The result of this community service activity is that the understanding of the Timuhun Village Office apparatus in serving population administration based on Cloud Computing technology has increased more than before education was carried out. In addition, the Timuhun Village Office has also created a digital form that can be accessed anytime anywhere via internet-based computer devices by village communities to request various population administration services. Another result of this activity is a module that is compiled in the form of a book to be studied again so that there is a sustainable use of Cloud Computing technology at the Timuhun Village Office.